2004
DOI: 10.1124/jpet.103.064709
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Inhibits ATP Release from Erythrocytes

Abstract: Erythrocytes have been reported to release ATP from intracellular stores into the surrounding environment in response to decreased oxygen tension and mechanical deformation. This erythrocyte-derived ATP can then act on purinergic receptors present on vascular endothelial cells, resulting in the synthesis and bidirectional release of nitric oxide (NO). NO released abluminally produces relaxation of vascular smooth muscle, thereby increasing vascular caliber, leading to a decrease in deformation-induced ATP rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
2
46
1
Order By: Relevance
“…Schwiebert et al also documented the appearance of P2X 7 to a significant degree at the mRNA level in primary cultures of human polycystic kidney disease (PKD) cells versus non-PKD human renal epithelial cell primary cultures as controls [101]. In a collaborative study with McCoy and Stanton, they showed expression of P2Y 1 and P2Y 2 as well as P2X 3 and P2X 4 in mIMCD-K2 cells [94]. In studies in mouse DCT cells by Quamme and coworkers and by Wingo and coworkers in mIMCD-3 cells, expression and function of both P2Y and P2X purinoceptors was concluded [92,93].…”
Section: Nucleotide and Nucleoside Receptor Expression Along The Nephronmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwiebert et al also documented the appearance of P2X 7 to a significant degree at the mRNA level in primary cultures of human polycystic kidney disease (PKD) cells versus non-PKD human renal epithelial cell primary cultures as controls [101]. In a collaborative study with McCoy and Stanton, they showed expression of P2Y 1 and P2Y 2 as well as P2X 3 and P2X 4 in mIMCD-K2 cells [94]. In studies in mouse DCT cells by Quamme and coworkers and by Wingo and coworkers in mIMCD-3 cells, expression and function of both P2Y and P2X purinoceptors was concluded [92,93].…”
Section: Nucleotide and Nucleoside Receptor Expression Along The Nephronmentioning
confidence: 99%
“…Within the glomerular capillaries, red and white blood cells alike are squeezed through these small capillaries and deformed in the process. Sprague and coworkers studied deformationinduced adenosine 5′ triphosphate (ATP) release in erythrocytes for many years, as have others [1][2][3]. With regard to mechanically released ATP, ATP and their metabolites are present in plasma at finite amounts, and the amount of nucleotides and nucleosides freely filtered at the glomerulus is likely to be low to negligible.…”
mentioning
confidence: 99%
“…Several reports published over recent years have shown that an increase in intracellular cyclic AMP (cAMP) concentration triggered ATP release from human erythrocytes (6,7). Receptor-mediated ATP release in human erythrocytes involves activation of heterotrimeric G proteins G s or G i/o (3,8,9). Regarding the G s pathway, activation of ␤-adrenergic receptors by various agonists was reported to stimulate adenylyl cyclase, with concomitant increases in cAMP levels and protein kinase A activity (6,10).…”
mentioning
confidence: 99%
“…All of these represent physiological conditions to which erythrocytes are exposed in the vasculature, e.g. when passing through constricted vessels or in the contracting striated muscle (3). Once in the extracellular medium, extracellular ATP (ATPe) 5 can trigger different cellular responses by interacting with P receptors on the cell surface while at the same time its concentration is controlled by the activities of one or more ectonucleotidases (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation